Influence of Bilingualism on Cognitive Abilities in Children in China - Yan, Zhang (International Journal of Linguistics, 2024)
Purpose: The aim of the study was to analyze the influence of bilingualism on cognitive abilities in children in China. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research on bilingualism and cognitive abilities in children in China has indicated several significant findings. Studies suggest that bilingualism can enhance executive functioning skills, such as cognitive flexibility and attention control, leading to improved problem-solving abilities. Additionally, bilingual children often demonstrate advanced metalinguistic awareness and language development, with proficiency in both their native language and a second language. Unique Contribution to Theory, Practice and Policy: Bilingual advantage hypothesis, socio-cultural theory & neuroplasticity theory may be used to anchor future studies on influence of bilingualism on cognitive abilities in children in China. Implement evidence-based instructional strategies educators should incorporate evidence-based instructional strategies that capitalize on the cognitive benefits of bilingualism. Advocate for bilingual education policies. Policymakers should advocate for the implementation of bilingual education policies that support language minority students' cognitive development.